GAMBARAN TINGKAT PENGETAHUAN TENTANG KEGAWATDARURATAN SEHARI-HARI PADA MAHASISWA FAKULTAS PARIWISATA UNIVERSITAS UDAYANA - Apriwani, Veronica Dwi; Saputra, I Kadek; Suindrayasa, I Made; Juniartha, I Gusti Ngurah (Coping: Community of Publishing in Nursing, 2024)
Bleeding, fainting, and choking incidents are everyday emergencies that can occur in tourist destinations. These incidents have increased due to poor initial handling by those closest to the location. In order to prevent the adverse effects of these events, someone who has a good understanding of everyday emergencies is needed, one of which is a student of the Faculty of Tourism. The purpose of this study was to determine the description of the level of knowledge about everyday emergencies in the 2020 Tourism Faculty students of Udayana University regarding bleeding, fainting, and choking. This research is a quantitative study with an observational descriptive design. The sample in this study were Faculty of Tourism Class of 2020 Udayana University students using simple random sampling technique as many as 158 students. Based on the results of the study, it was found that the majority of respondents were 21 years old (59.5%), female (62%), the experience of never seeing a daily emergency about bleeding was (56.3%), had seen a fainting incident (80.4%), and had never seen a choking incident (46.2%) with a sufficient level of knowledge. Experience of never helping with daily bleeding emergencies amounted to (81.6%), having helped fainting events amounted to (61.4%), and never seeing choking events amounted to (61.4%) with a moderate level of knowledge. The source of information obtained mostly through intermediaries (70.3%) with a sufficient level of knowledge. In terms of knowledge, it was found that the majority of students had a moderate level of knowledge (59.5%). It can be concluded that the level of knowledge of the 2020 class of Tourism Faculty students at Udayana University is in the moderate category. Students are advised to gain basic knowledge about daily emergencies independently by obtaining information from various sources either intermediaries or without intermediaries about bleeding, fainting, and choking.